Study on the bacterial and archaeal community structure and diversity of activated sludge from three wastewater treatment plants. (October 2018) - Qin, Hui; Ji, Bin; Zhang, Shufei; Kong, Zehua
Abstract: In this study, the bacterial and archaeal communities along with their functions of activated sludge from three wastewater treatment plants were investigated by Illumina MiSeq Platform. The treatment processes were modified A/A/O, DE oxidation ditch and pre-anaerobic carrousel oxidation ditch, respectively. The taxonomic analyses showed that Proteobacteria was the predominant bacterial phylum, and Nitrosospira was the dominant nitrification genus. Candidatus Accumulibacter was abundant in DE oxidation ditch process, and the main archaea communities were methanosaeta -like species which had the capability to anaerobic ammonia oxidation. The results illustrated that anaerobic ammonium oxidation played an important role in the nitrogen metabolism and there might be other unknown phosphate-accumulating organisms (PAOs) performing phosphorus removal in activated sludge. The predicted function analyses indicated that both bacteria and archaea were involved in nitrification, denitrification, ammonification and phosphorus removal processes, and their relative abundance varied metabolic modules differed from each other. Highlights: Bacterial and archaeal communities in activated sludge were simultaneously investigated by Illumina MiSeq Platform. Bacteria and archaea from different communities had similar functional classification in contaminant metabolism. Proteobacteria was the predominant bacterial phylum and archaea community was dominated by methanosaeta -like species. Treatment process had a greater impacts on the functions of archaea than bacteria.